2008
DOI: 10.1016/j.cell.2008.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of the Longevity-Promoting Factor SKN-1 by Insulin-like Signaling in C. elegans

Abstract: Insulin/IGF-1-like signaling (IIS) is central to growth and metabolism and has a conserved role in aging. In C. elegans, reductions in IIS increase stress resistance and longevity, effects that require the IIS-inhibited FOXO protein DAF-16. The C. elegans transcription factor SKN-1 also defends against oxidative stress by mobilizing the conserved phase 2 detoxification response. Here we show that IIS not only opposes DAF-16 but also directly inhibits SKN-1 in parallel. The IIS kinases AKT-1, -2, and SGK-1 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
973
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 830 publications
(1,019 citation statements)
references
References 42 publications
39
973
4
3
Order By: Relevance
“…Tullet et al . (2008) indicated that the transcription network regulated by SKN‐1 promotes longevity and is an important direct target of IIS. SKN‐1 represents a connection between the development of the digestive system and one of its most basic functions – resistance to oxidative and xenobiotic stresses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tullet et al . (2008) indicated that the transcription network regulated by SKN‐1 promotes longevity and is an important direct target of IIS. SKN‐1 represents a connection between the development of the digestive system and one of its most basic functions – resistance to oxidative and xenobiotic stresses.…”
Section: Resultsmentioning
confidence: 99%
“…The skn‐1 mutant of C. elegans shows decreased resistance to oxidative stress and a shortened lifespan. In contrast, C. elegans mutants overexpressing SKN‐1, which constitutively localizes to the nuclei of intestinal cells, show increased resistance to oxidative stress and increased longevity (An & Blackwell, 2003; An et al ., 2005; Tullet et al ., 2008). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All mutants had previously been reported to extend lifespan (Friedman & Johnson, 1988; Hertweck, Gobel, & Baumeister, 2004; Kenyon et al., 1993; McElwee, Bubb, & Thomas, 2003; Murphy, Lee, & Kenyon, 2007; Paradis, Ailion, Toker, Thomas, & Ruvkun, 1999; Tullet et al., 2008; Zhang et al., 2008). However, the sgk‐1 mutant has been observed to have variable lifespan (Chen, Guo, Dumas, Ashrafi, & Hu, 2013; Mizunuma, Neumann‐Haefelin, Moroz, Li, & Blackwell, 2014; Xiao et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, NHR‐49 and SKN‐1 are both important in stress conditions and in long‐lived glp‐1 mutants, but partner with MDT‐15 to coordinate expression of distinct gene sets that may be more important under particular conditions. For example, in long‐lived daf‐2 /insulin receptor mutants, where skn‐1 is important, but nhr‐49 dispensable for the increase in lifespan (Ratnappan et al., 2014; Tullet et al., 2008), the requirement for mdt‐15 may exclusively reflect MDT‐15's function as a SKN‐1 coregulator (Goh et al., 2014). …”
Section: Discussionmentioning
confidence: 99%